2006
DOI: 10.1111/j.1365-2095.2006.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Polka-dot grouper, Cromileptes altivelis, can utilize dietary fat efficiently

Abstract: Polka‐dot grouper, Cromileptes altivelis, a highly‐prized fish in Asian live fish markets, is a slow‐growing species. Long‐chain (LCF) or medium‐chain fatty acids (MCF) were fed to polka‐dot grouper (14 g initial weight) for 8 weeks to see if growth could be stimulated. Five dietary treatments were compared: a control diet with low fat (56 g kg−1) or diets that contained either moderate (150 g kg−1) or high (300 g kg−1) supplements of fat that were added either as olive oil for the LCF or coconut oil for the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 36 publications
(79 reference statements)
7
34
0
2
Order By: Relevance
“…Besides their role as an energy source, lipids have been shown to act as important signaling molecules in mammals (28). In fish, high levels of circulating lipids have been traditionally associated with reduced food intake (15,17,32,49,51,56), while more recently, a deleterious effect on glucose homeostasis has been described in rainbow trout fed a high-fat diet (12). However, these effects had never been evaluated before using individual FA.…”
Section: Discussionmentioning
confidence: 96%
“…Besides their role as an energy source, lipids have been shown to act as important signaling molecules in mammals (28). In fish, high levels of circulating lipids have been traditionally associated with reduced food intake (15,17,32,49,51,56), while more recently, a deleterious effect on glucose homeostasis has been described in rainbow trout fed a high-fat diet (12). However, these effects had never been evaluated before using individual FA.…”
Section: Discussionmentioning
confidence: 96%
“…This occurred for instance in rainbow trout (Peragón et al, 2000; Rasmussen et al, 2000; Gélineau et al, 2001; Forsman and Ruohonen, 2009; Figueiredo-Silva et al, 2012c; Saravanan et al, 2013), chinook salmon (Silverstein et al, 1999), polka-dot grouper (Williams et al, 2006), Senegalese sole (Bonacic et al, 2016) or grass carp (Li et al, 2016). Moreover, enhanced lipid storage is also usually associated with a reduced food intake (Shearer et al, 1997; Silverstein et al, 1999; Johansen et al, 2002, 2003).…”
Section: Impact Of Nutrient Sensing On Food Intake Regulationmentioning
confidence: 99%
“…The dietary lipid was predominantly from either coconut oil for MCFA, or olive oil for LCFA. The diets used were the same diets used in a previous growth assay (Williams et al. 2002b) in which olive oil was chosen as the source of LCFA because of its very low content of n‐3 series of polyunsaturated fatty acids (PUFA) (Table 2).…”
Section: Diets and Radioisotope‐labelled Fatty Acidsmentioning
confidence: 99%
“…Recent studies with polka dot grouper have indicated that this species increased protein retention when 150 g kg −1 , but not 300 g kg −1 fat, in the form of LCFA, was added to the diet. However, when 300 g kg −1 LCFA was added to the diet, or when 150 or 300 g kg −1 MCFA were added to the diet, food intake and growth were severely depressed (Williams et al. 2002b).…”
Section: Introductionmentioning
confidence: 99%